INTEGRASI NILAI-NILAI EKONOMI ISLAM DALAM KURIKULUM: PENDIDIKAN EKONOMI DI SEKOLAH MENENGAH - Gigih Hadi Nugroho Said; Hilalludin Hilalludin (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
Economic education plays a strategic role in shaping students’ knowledge, attitudes, and skills to face the dynamic challenges of the modern economic world. However, the current curriculum in Indonesian secondary schools tends to adopt a conventional economic paradigm, focusing more on technical and market-based aspects, while neglecting the integration of Islamic economic values. This study aims to fill the gap by developing a model for integrating Islamic economic values—such as prohibition of riba, justice in distribution, zakat, waqf, and ethical business conduct—into the economics curriculum. Unlike previous studies that mainly focused on Islamic economics in financial institutions, this research addresses the practical implementation of these values in formal education settings. Motivated by the urgency to produce not only academically competent graduates but also morally sound individuals, the study uses a qualitative approach through library research and curriculum document analysis. The findings reveal that integrating Islamic economic principles can provide a more holistic economic understanding, bridging ethical-spiritual dimensions with modern economic practices. Furthermore, the study proposes a systematic model of curriculum integration involving content, teaching methods, and evaluation strategies. The results hold significant implications for policymakers, educators, and curriculum developers in shaping an economic education that aligns with Indonesia’s religious and cultural values.